Relationship between right atrium area and right ventricular ejection fraction on magnetic resonance imaging: comparison with other prognostic markers in patients with pulmonary arterial hypertension - Mello,Marcelo M. (2019)
Abstract Objective: To compare the right atrium (RA) area and right ventricular ejection fraction (RVEF) with other known prognostic markers in patients with pulmonary arterial hypertension (PAH). Materials and Methods: This was a retrospective study of 74 patients diagnosed with PAH by right heart catheterization at a referral center between January 2018 and May 2018. All of the patients underwent cardiac magnetic resonance imaging (MRI) within 3 months of the right heart catheterization (RHC), as well as undergoing echocardiography, a 6-minute walk test, and determination of the level of N-terminal pro-brain natriuretic peptide (NT-proBNP) within a month of the RHC. We attempted to determine whether the cardiac MRI-derived RA area correlated with ions between RVEF and RA area measured by that determined by echocardiography, as well as whether the cardiac MRI-derived RA area and RVEF correlated with the 6-minute walk distance and NT-proBNP level. Results: The MRI-derived RA area demonstrated a weak correlation with the pulmonary vascular resistance measured by RHC (r = 0.268; p = 0.055) and a moderate correlation with the NT-proBNP (r = 0.429; p = 0.003). All correlations between clinical characteristics and the RVEF were statistically significant. In the univariate linear analysis, the RVEF showed stronger correlations with the clinical characteristics than did the RA area. Conclusion: In patients with PAH, cardiac MRI-derived RVEF appears to correlate more strongly with other prognostic factors than does RA area.